Science as a game: conceptual model and application in scientific software design. Issue 4 (2nd October 2022) - Queiroz, Francisco; Lonsdale, Maria; Spitz, Rejane
ABSTRACT: Scientific inquiry is often described as, and compared to, a game. This paper expands on that analogy to propose a conceptual model of scientific practice built upon Jesper Juul's game definition, and informed by parallels between the two activities collected from selected works from history and philosophy of science. Moreover, the paper presents a design method, based on the model described, for fostering creative solutions in scientific software user interface design. Results from pilot case studies suggest both model and method are helpful, allowing participants to describe requirements and ideate solutions, as well providing a framework for the exploration of the game-science analogy within the context of scientific research conducted through computational resources.